«Unclassified materials» of the practicing doctor (Эндодонтия Today)
The presented article covers a range of issues arising in daily clinical practice of an endodontist. It is not a study in the classic sense of this word. Author, a therapist with extensive experience on the base of her own clinical cases shares the thoughts regarding methods and technologies of endodontic treatment, arises the discussion regarding the concepts of success and failure in endodontics. The article is based on problem-oriented principle, it encourages readers to reflect together with the author, has written on an interesting and even artistic language. Extremely useful material contributes to the development of clinical thinking of the practitioners and it is especially valuable for the beginners in dentistry.